Combinations of Random Variables
Sometimes, it is necessary to add or subtract
random variables. When this occurs, it is useful to know the
mean and variance of the result.
Recommendation: Read the
sample problems at the end of the lesson.
This lesson introduces some useful equations, and the sample
problems show how to apply those equations.
Sums and Differences of Random Variables: Effect on the Mean
Suppose you have two variables: X with a mean of μx
and Y with a mean of μy. Then, the mean of the sum of
these variables μx+y and the mean of the difference
between these variables μx-y are given by the
μx+y = μx + μy
μx-y = μx - μy
The above equations for general variables also apply to random variables.
If X and Y are random variables, then
E(X + Y) = E(X) + E(Y)
E(X - Y) = E(X) - E(Y)
where E(X) is the expected value (mean) of X, E(Y) is the expected value
of Y, E(X + Y) is the expected value of X plus Y, and E(X - Y) is the
expected value of X minus Y.
Sums and Differences of Independent Random Variables: Effect on Variance
Suppose X and Y are independent random variables. Then,
the variance of (X + Y) and the variance of (X - Y) are
described by the following equations
Var(X + Y) = Var(X - Y) = Var(X) + Var(Y)
where Var(X + Y) is the variance of the sum of X and Y, Var(X - Y) is
the variance of the difference between X and Y, Var(X) is the
variance of X, and Var(Y) is the variance of Y.
Note: The standard deviation (SD) is always equal to the square root of
the variance (Var). Thus,
SD(X + Y) = sqrt[ Var(X + Y) ]
SD(X - Y) = sqrt[ Var(X - Y) ]
Test Your Understanding of This Lesson
The table on the right shows the joint probability distribution between
two random variables - X and Y. (In a joint probability distribution
table, numbers in the cells of the table represent the probability
that particular values of X and Y occur together.)
What is the mean of the sum of X and Y?
(E) None of the above.
The correct answer is D. The solution requires three computations: (1)
find the mean (expected value) of X, (2) find the mean (expected value)
of Y, and (3) find the sum of the means. Those computations are
shown below, beginning with the mean of X.
E(X) = Σ [ xi * P(xi) ]
E(X) = 0 * (0.1 + 0.1) + 1 * (0.2 + 0.2) + 2 * (0.2 + 0.2) = 0 + 0.4 + 0.8 = 1.2
Next, we find the mean of Y.
E(Y) = Σ [ yi * P(yi) ]
E(Y) = 3 * (0.1 + 0.2 + 0.2) + 4 * (0.1 + 0.2 + 0.2) = (3 * 0.5) + (4 * 0.5) = 1.5 + 2 = 3.5
And finally, the mean of the sum of X and Y is equal to the sum of
the means. Therefore,
E(X + Y) = E(X) + E(Y) = 1.2 + 3.5 = 4.7
Note: A similar approach is used to find differences between
means. The difference between X and Y is
E(X - Y) = E(X) - E(Y) = 1.2 - 3.5 = -2.3; and the difference
between Y and X is E(Y - X) = E(Y) - E(X) = 3.5 - 1.2 = 2.3
Suppose X and Y are independent random variables. The variance of
X is equal to 16; and the variance of Y is equal to 9.
Let Z = X - Y.
What is the standard deviation of Z?
(E) It is not possible to answer this question, based on the
The correct answer is B. The solution requires us to recognize that
Variable Z is a combination of two independent
random variables. As such,
the variance of Z is equal to the variance of X plus the variance
Var(Z) = Var(X) + Var(Y) = 16 + 9 = 25
The standard deviation of Z is equal to the square root of the
variance. Therefore, the standard deviation is equal to the
square root of 25, which is 5.